GENERAL CHARACTERISTICS OF IMPOSING PUNISHMENT ON MINORS - Israilov Dilshod Shavkatovich (PT. Antis International Publisher, 2024)
General Background: This article examines the complexities of sentencing juvenile offenders, emphasizing the need for a nuanced approach to punishment that reflects their developmental characteristics. Specific Background: Juveniles exhibit unique socio-psychological traits that necessitate distinct legal considerations, leading to ongoing debates about fair punishment in the context of their age and circumstances. Knowledge Gap: Despite existing regulations, there is a lack of comprehensive analysis on how current laws effectively address the principles of fairness and proportionality in juvenile sentencing. Aims: The research aims to evaluate the legal framework surrounding juvenile punishment in Uzbekistan, identifying potential enhancements to better protect minors while ensuring accountability. Results: The study reveals that the prevailing legal framework prioritizes both accountability and rehabilitation, advocating for age-appropriate punishments that consider the individual context of juvenile offenders. It aligns with Voltaire’s philosophy of crime prevention and Uzbekistan’s legislative intent to balance responsibility with moral correction. Novelty: This research contributes to the discourse on juvenile justice by critically assessing the intersection of legal norms and socio-psychological factors influencing sentencing. Implications: By adopting a preventative approach to juvenile delinquency, the judicial system can effectively reduce recidivism and promote social reintegration, thereby fostering a more stable environment and mitigating long-term criminal behavior among minors. Limitations: The study's reliance on legislative documents and court procedures limits its ability to longitudinally assess the impact of penalties on behavior change. Further Research: Future investigations should explore the effectiveness of rehabilitative measures and alternative restorative justice practices as more humane approaches to juvenile offending.